2021
DOI: 10.2196/32708
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, Feasibility, and Quality of Telehealth for Adolescent Health Care Delivery During the COVID-19 Pandemic: Cross-sectional Study of Patient and Family Experiences

Abstract: Background Data regarding the acceptability, feasibility, and quality of telehealth among adolescents and young adults (AYA) and their parents and caregivers (caregivers) are lacking. Objective The aim of this study was to assess the noninferiority of telehealth versus in-person visits by comparing acceptability with respect to efficiency, effectiveness, equity, patient-centeredness, and confidentiality. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…Overall, the literature suggests that patients were disposed to undertake virtual therapy and recounted largely positive experiences with their eating disorder treatment. Authors found no differences in telehealth visit completion rates among patients [169,172] and some studies further suggested unexpected advantages of telehealth such as a greater level of familial involvement in treatment [159,202]. However, despite the advantages listed above, many patients reported preferring the face-to-face over the online type of appointment [159,169,170].…”
Section: The Role Of Telemedicine For the Mental Health Of Young Peop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the literature suggests that patients were disposed to undertake virtual therapy and recounted largely positive experiences with their eating disorder treatment. Authors found no differences in telehealth visit completion rates among patients [169,172] and some studies further suggested unexpected advantages of telehealth such as a greater level of familial involvement in treatment [159,202]. However, despite the advantages listed above, many patients reported preferring the face-to-face over the online type of appointment [159,169,170].…”
Section: The Role Of Telemedicine For the Mental Health Of Young Peop...mentioning
confidence: 99%
“…For both parameters, the highest percentages were recorded in states with high rates of coronavirus positivity and high rates of unmet need. Also, a cross-sectional web-based survey conducted specifically among adolescents and young adults by Wood et al [172] revealed that telehealth was highly acceptable among them and caregivers. A total of 55 patients and 123 caregivers rated telehealth as noninferior to in-person visits with respect to privacy, communication, managing medication questions, discussing test results, mood, and mental health.…”
Section: The Role Of Telemedicine For the Mental Health Of Young Peop...mentioning
confidence: 99%
“…The COVID-19 pandemic has taken the lives of over 1,000,000 Americans and strained the capacity of healthcare professionals and systems to care for complex patients [ 1 – 3 ]. Healthcare systems have reduced patient loads to limit in-person contact and preserve resources for COVID-19 care, but these changes have limited capacity for cancer care [ 4 , 5 ]. Shifting to telehealth has been challenging for cancer patients whose care may require laboratory tests or hands-on examination [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare systems have reduced patient loads to limit in-person contact and preserve resources for COVID-19 care, but these changes have limited capacity for cancer care [ 4 , 5 ]. Shifting to telehealth has been challenging for cancer patients whose care may require laboratory tests or hands-on examination [ 4 , 5 ]. While some patients are hesitant to start or continue cancer care during the pandemic, expedient cancer care is still a priority.…”
Section: Introductionmentioning
confidence: 99%
“…Given the paucity and heterogeneity of research on this topic, the rapid and widespread COVID-19-induced implementation of telehealth in European youth mental health services provided a unique opportunity to examine the perspectives of young people and their parents on remote mental health care delivery. Many articles during this period have focused on the experience of health professionals [26,27] and family caregivers [28], but very few on the crosssectional perspectives of adolescents and their parents [29]. The perspectives of both groups are critical for assessing multiple aspects of telemedicine services, including therapeutic alliance quality, communication quality, impact on family routines, and overall satisfaction and acceptability.…”
Section: Introductionmentioning
confidence: 99%